Dutch Oncology COVID-19 consortium: Outcome of COVID-19 in patients with cancer in a nationwide cohort study. (December 2020) - de Joode, Karlijn; Dumoulin, Daphne W.; Tol, Jolien; Westgeest, Hans M.; Beerepoot, Laurens V.; van den Berkmortel, Franchette W.P.J.; Mutsaers, Pim G.N.J.; van Diemen, Nico G.J.; Visser, Otto J.; Oomen-de Hoop, Esther; Bloemendal, Haiko J.; van Laarhoven, Hanneke W.M.; et al.
Abstract: Aim of the study: Patients with cancer might have an increased risk for severe outcome of coronavirus disease 2019 (COVID-19). To identify risk factors associated with a worse outcome of COVID-19, a nationwide registry was developed for patients with cancer and COVID-19. Methods: This observational cohort study has been designed as a quality of care registry and is executed by the Dutch Oncology COVID-19 Consortium (DOCC), a nationwide collaboration of oncology physicians in the Netherlands. A questionnaire has been developed to collect pseudonymised patient data on patients' characteristics, cancer diagnosis and treatment. All patients with COVID-19 and a cancer diagnosis or treatment in the past 5 years are eligible. Results: Between March 27th and May 4th, 442 patients were registered. For this first analysis, 351 patients were included of whom 114 patients died. In multivariable analyses, age ≥65 years ( p < 0.001), male gender ( p = 0.035), prior or other malignancy ( p = 0.045) and active diagnosis of haematological malignancy ( p = 0.046) or lung cancer ( p = 0.003) were independent risk factors for a fatal outcome of COVID-19. In a subgroup analysis of patients with active malignancy, the risk for a fatal outcome was mainly determined by tumour type (haematological malignancy or lung cancer) and age (≥65 years). Conclusion: The findings in this registry indicate that patients with a haematological malignancy or lung cancer have an increased risk of a worse outcome of COVID-19. During the ongoing COVID-19 pandemic, these vulnerable patients should avoid exposure to severe acute respiratory syndrome coronavirus 2, whereas treatment adjustments and prioritising vaccination, when available, should also be considered. Highlights: Patients with cancer might have an increased risk for severe outcome of coronavirus disease 2019 (COVID-19). This nationwide study investigated risk factors for fatal outcome of COVID-19. Among 442 registered patients with cancer, 32.3% of patients died of COVID-19. Haematological malignancy and lung cancer increased the risk of fatal outcome. These results can guide treatment and vaccination decisions in patients with cancer.